2006
DOI: 10.2302/kjm.55.96
|View full text |Cite
|
Sign up to set email alerts
|

Duodenal Carbonic Anhydrase: Mucosal Protection, Luminal Chemosensing, and Gastric Acid Disposal

Abstract: Abstract. The duodenum serves as a buffer zone between the stomach and jejunum. Over a length of only 25 cm, large volumes of strong acid secreted by the stomach must be converted to the neutral-alkaline chyme of the hindgut lumen, generating large volumes of CO 2 , which the duodenum then absorbs. The duodenal mucosa consists of epithelial cells connected by low-resistance tight junctions, forming a leaky epithelial barrier. Despite this high permeability, the epithelial cells, under intense stress from lumin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 88 publications
0
15
0
Order By: Relevance
“…Jacob et al recognized that this pathway was not essential for a full forskolin-stimulated secretory response as long as Na ϩ HCO 3 Ϫ cotransporter was fully active, but was not able to provide HCO 3 Ϫ for secretion if Na ϩ HCO 3 Ϫ cotransporter was pharmacologically inhibited (10). The group of Kaunitz and Akiba first recognized the role of CAs in duodenal ''acid sensing'' (24). In a series of papers, they used CA inhibitors with differential membrane permeability, luminal acid or CO 2 application, and measured enterocyte pH i , DBS, as well as pH and pCO 2 changes in the portal venous blood and recognized the importance of CAs in the HCO 3 Ϫ secretory response to high pCO 2 (25).…”
Section: Discussionmentioning
confidence: 99%
“…Jacob et al recognized that this pathway was not essential for a full forskolin-stimulated secretory response as long as Na ϩ HCO 3 Ϫ cotransporter was fully active, but was not able to provide HCO 3 Ϫ for secretion if Na ϩ HCO 3 Ϫ cotransporter was pharmacologically inhibited (10). The group of Kaunitz and Akiba first recognized the role of CAs in duodenal ''acid sensing'' (24). In a series of papers, they used CA inhibitors with differential membrane permeability, luminal acid or CO 2 application, and measured enterocyte pH i , DBS, as well as pH and pCO 2 changes in the portal venous blood and recognized the importance of CAs in the HCO 3 Ϫ secretory response to high pCO 2 (25).…”
Section: Discussionmentioning
confidence: 99%
“…These mechanisms coordinately regulate mucus and HCO 3 – secretion, pH i and cellular buffering, and submucosal neuronal activation and blood flow responses. Since duodenal luminal pH rapidly changes between 2 and 7 as a result of the constant mixture of secreted HCO 3 – with jets of antrally-propelled gastric acid, the duodenal mucosa must rapidly adjust its defense mechanisms according to luminal pH [5]. …”
Section: Duodenal Acid/co2 Sensingmentioning
confidence: 99%
“…8,10 The metalloenzyme CA catalyzes the interconversion of CO 2 and HCO 3 À , which is important for urease-mediated acid resistance in the gastric environment. 9 This journal is © The Royal Society of Chemistry 2014 with time and followed similar excretion kinetics with that of 13 C-enriched labelled urea. It is therefore noteworthy that the excretion kinetics of d DOB 18 O& followed a similar pattern regardless of the isotopic labelled substrate.…”
Section: Resultsmentioning
confidence: 55%
“…d DOB 13 C&, is usually $2&, is strongly associated with the presence of H. pylori infection in human stomach. 7 However, several reports 8,9 suggest that H. pylori encodes two different forms of the metalloenzyme carbonic anhydrase (a-CA and b-CA), which plays an important role in the interconversion of carbon dioxide and bicarbonate (CO 2 + H 2 O 4 H + + HCO 3 ), as well as for maintaining the urease activity in the human gastrointestinal tract. 10-12 Some authors [13][14][15] have also demonstrated that the oxygen-16 ( 16 O) isotope in 12 In this article, we report for the rst time, the potential links between the 18 O-isotope of breath CO 2 and H. pylori infections by exploiting the time-dependent excretion kinetics of the 18 O/ 16 O isotope ratios of CO 2 in breath samples from individuals with and without H. pylori infections.…”
Section: Introductionmentioning
confidence: 99%